The Effect of Intellectual Capital on Company Value in Industries Affected by Covid-19 - Fatmasari, Yuli; Hisamuddin, Nur; Wardhaningrum, Oktaviani Ari (Accounting Department, Faculty of Business and Management, Universitas Internasional Batam, 2023)
Purpose - This study aims to examine the effect of intellectual capital on company value in industries affected by covid-19 and to examine whether there are differences in intellectual capital between the two industries affected by covid-19. Research Method - This research is quantitative research. The sample was selected based on a purposive sampling technique with certain criteria. After the sample selection process was carried out, it resulted in 62 total data samples obtained from 18 hotel, restaurant, and tourism industry companies and 13 health industry companies. The data covers the period from 2020-2021. The data analysis technique used is descriptive statistics with simple linear regression and different independent sample t-tests. Findings - The results of the simple linear regression test show that intellectual capital has a significant effect on firm value. The results of the independent sample t-test show that there are differences between intellectual capital in the hotel, restaurant, and tourism industry and the health industry. Implication - Company value is a representation of the state of a company, where potential investors will give a special assessment related to the good and bad performance of the company. Nevertheless, investors should consider the company’s intellectual capital too. Moreover, result of this research shows that the Covid-19 outbreaks make a significant difference to company value. Investors should take this into a concern in deciding investment decision. Keywords: Intellectual Capital, Company Value, Covid-19